Antibacterial Potency of Honey - Najla A. Albaridi (International Journal of Microbiology)
Despite the developments in controlling infectious disease around the world, they are still the second biggest cause of morbidity and mortality due in part to the increase in drug resistance among large numbers of the bacterial strains. This means that new strategies are needed to prevent and treat infectious disease. As a result, several ancient methods have been re-evaluated and the substances/procedures employed historically to cure diseases are now attracting renewed scientific attention. Honey is one such product that used to be widely used to combat bacteria. This review covers the antibacterial activity of honey, its use in the treatment of infection and diseases, and the features that are relevant to its activity.